Esophageal perforation caused by a central venous catheter: A case report and literature review. Issue 2 (4th December 2019) - Chen, Wei‐Ming; Chiang, Ming‐Shih; Wang, Po‐Chang; Wei, Kuo‐Liang; Tung, Shui‐Yi; Chang, Te‐Sheng; Hung, Chao‐Hung
Abstract: Malposition of the central venous catheter is rare but may cause morbidity and mortality. Here, we presented a male patient who suffered from a misplaced central venous catheter into the esophagus and caused perforation. We removed the misplaced central venous catheter directly after evaluated by computed tomography. We provided an available method to evaluate and solve this problem after literature view. In catheter‐related esophageal perforation patient, conservative treatment is an optional therapy after removed the misplaced catheter without fluoroscopy guided according to clinical presentation.